Profil Atlet Tolak Peluru Cabang Olahraga Atletik - Saputro, Irfan Toni; Rumini, Rumini (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine the anatomical structure of the body of a shot put athlete. The research method used in this study is a quantitative approach. The sampling technique uses (purposive) or based on the purpose of not having overlapping data when conducting data analysis. The results of the research conducted showed that the condition of the shot put athlete who took part in the 2021 POPNAS selection in Central Java was said to be moderate with a BMI of 28.08 so it was said to be obese and with the results of a speed of 5.2 seconds, running 30 meters was said to be moderate, flexibility 16 cm, agility 12 seconds, up and down 59 times. . With the psychological level of athletes in the good category of shot put with an average value of 72.8%, for muscle explosive power of 3.95 it is said to be moderate. The conclusion is not only body posture but physical condition is very taken into account in this study, the physical condition of the shot put athletes who took part in the 2021 POPNAS selection in Central Java can be said to be with moderate criteria. Physical condition is very important especially for an athletic athlete in the shot put number because it is to balance a large body posture.